If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2y + -16 = x Reorder the terms: 4 + -16 + -2y = x Combine like terms: 4 + -16 = -12 -12 + -2y = x Solving -12 + -2y = x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -2y = 12 + x Combine like terms: -12 + 12 = 0 0 + -2y = 12 + x -2y = 12 + x Divide each side by '-2'. y = -6 + -0.5x Simplifying y = -6 + -0.5x
| 5j-(-2)=-3 | | -6-6x=-5x+5 | | 4k+(-9)=0 | | 7m-3=8 | | 8+3x=-2x-22 | | 12x-9y=360 | | 5x=5-3y | | -3x+4(7x-7)=97 | | -4v+2(v+2)=10 | | 47=5x-2(-3x+4) | | 5x+20=3x+8 | | 249=2x+x^2 | | 0.2c=6 | | 0.2=6 | | 5x-3(2x+8)=-30 | | 130+5= | | -32=-20k+40-25 | | 3(y-10)=6 | | 10p+8=-19p-19 | | 10+8=-19p-19 | | 20p+8=-19p-19 | | 20p+8=-15p-19 | | 20p+4=-10p-19 | | 15p+8=-19p-19 | | 20p+4=-19p-19 | | 20p+2=-19p-19 | | -2-2(1-x)=-25-x | | 3-4h=5-2h | | -20p+8=-19p-19 | | -20p+11=-19p-19 | | 4c-3G-2c+c+1+2c= | | 28=-4x-6(x+7) |